Landscape phytosociology and biodiversity conservation management in the eastern Dahra - (:unkn) unknown (My University, 2022)
The Mediterranean vegetation landscape, whose formation depends mainly on human action, is currently threatened by the increase of anthropic influences that cause a profound modification of the landscape. Forest ecosystems are being replaced by anthropized ecosystems, threatening the biodiversity of this region.This work is conducted within the framework of the management and conservation of biodiversity in the Mediterranean region, in general, and that of Algeria in particular. It consists of the typology and mapping of vegetation and vegetation series of the eastern Dahra, in order to better understand the importance of disturbances of anthropogenic origin and to propose the establishment of an adapted and reasoned management.The study area was chosen as a "pilot" region because of its geomorphological and orographic heterogeneity, the anthropic pressure it is subject to and the particularities of its vegetation characterized by sensitive, unstable and often degraded formations.The landscape phytosociology allows on the one hand the study and the description of the dynamic trajectories of thevegetation series and on the other hand to evaluate the weight of the anthropization in the shaping of the vegetation landscapes.The landscape phytosociological method, used for more than three decades in Europe, remains little developed in North Africa and more specifically in Algeria. This work constitutes a first basis that could be pursued to generalize this approach on the whole North African perimeter.This study allows to identify and map vegetation (actual and potential) and vegetation series and to understand their dynamic trajectory and identifies areas of conservation concern. It provides a tool for biodiversity management and conservation stakeholders, that allows to determine the degree of conservation or degradation of vegetation, to identify areas impacted by human activities by identifying their distance from the natural potential vegetation.
Keywords: African Research